ANALISIS SIRKULASI UDARA PADA SISTEM PERNAFASAN MANUSIA MENGGUNAKAN METODE VOLUME HINGGA - Putra, Andhi Septian Hadi; Suharto, Suharto; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2017)
Abstract. In human respiration there are several factors that can affect the speed of air flow. This study describes the effect of initial velocity and Prandtl numbers on the velocity of airflow in the human respiratory system. In this study built airflow equations in the human respiratory system built from the mass continuity equation, changes in momentum and energy using the volume method up. Then made a disctritization of the flow of air circulation in the human respiratory system. Next make the air circulation program on the human respiratory system using MATLAB and FLUENT applications. The result of this research is airflow equation with error less than 1% and air circulation simulation program on human respiratory system. Keywords : Air Circulation, Finite Volume Method